Letter (copy) : Ricardo Zabalza - Citrine, Walter, 1887-1983
013-0115-001 Interntional. WMC/WJB/DT/461. 12th January, 1940. Mr. Orencio Labrador, c/o, Mrs. Peech, Pugle-Frith, Cudham, KENT. Dear Sir, RICARDO ZABALZA. With further reference to my letter of the 4th instant, I have now received a promise from the Authorities that they will do all they can to deter the Government of Spain from the course of action at which it is embarked. It is pointed out that from various causes, tendencies are beginning to appear in our favour in Spain and there is hope that they will bring about a cessation of the present methods of repression. Yours faithfully, General Secretary. 292/946/13/115